177k views
1 vote
S = 1 / g t ² π, solve for t​

User Fathi
by
5.9k points

2 Answers

4 votes


\bf S=\cfrac{1}{2}gt^2\pi \implies S = \cfrac{gt^2\pi }{2}\implies 2S=gt^2\pi \implies \cfrac{2S}{g\pi }=t^2\implies \sqrt{\cfrac{2S}{g\pi }}=t

User Rpj
by
5.9k points
1 vote


s = \frac{1}{g {t}^(2)\pi }

multiply through by


g {t}^(2) \pi


s * g {t}^(2) \pi = \frac{1}{g {t}^(2) \pi} * g {t}^(2) \pi


sg {t}^(2) \pi = 1

dividing through by

sgπ


{t}^(2) = (1)/(sg\pi)


t = \sqrt{ (1)/(sg\pi) }

User Elle
by
5.9k points